Sexual behaviour of Advanced Level students in Southern Sri Lanka - B. Perera; P. H. G. Fonseka (Journal of the College of Community Physicians, 1998)
Objectives: To identify the prevalence of different types of sexual experiences among advanced Level students in the district of Galle in Sri Lanka and to identify the students' attitudes and skills in condom use.   Methodology: This is a cross sectional survey. Data was collected from 446 advanced level students in the district of Galle using a self-administered questionnaire.   Results: Among 446 students surveyed, approximately 50% of male students and 30% of female students were sexually active at the time of the survey. Male students were significantly more likely than female students to indulge in sex (11.5% vs. 2.7% for sexual intercourse experience). Science stream students were less likely to have exposure in sexual activities compared to Commerce and Arts stream students. Moreover, economically privileged students seems to have indulged in sexual activities more, compared to others. Among those who were involved in risky sexual activities, the use of condoms was considerably low.   Conclusions: Among late teenagers in the school going population, sexual health plays a major role in promoting their overall health. Existing sexual health programmes targeted at school children need to be evaluated continuously and attention should be paid to improve students' attitudes and skills in safer sex methods.